Evaluation of Engineering Geological Conditions for Slope Stability Analysis of Diversion Tunnel Portal of Jlantah Dam, Karanganyar, Central Java - Yayi Ismanda; I Gde Budi Indrawan; Heru Hendrayana (Geological Engineering Department Universitas Gadjah Mada, 2023)
This paper presents the research results carried out to analyze the slope stability of the diversion tunnel portal of Jlantah Dam based on the quality of the rock mass. The classification of the rock mass quality at the tunnel location refers to the Geological Strength Index (GSI) method while the analysis of portal slope stability is modelled numerically with the element method using Phase2 software. The modelling of the tunnel portal slope design with and without earthquake load was carried out to obtain the safety factor (SF) value. The results showed that the study area consists of residual soil, andesite breccia and lapilli tuff rocks with rock mass quality based on the GSI value ranging from poor to fair. The inlet portal slope is composed of rocks that have poor and fair mass quality while the inlet section is composed of rocks that have poor mass quality. The SF value>1.3 for conditions without earthquake effect was achieved on slope design 1V:1.5H and SF value>1.1 for conditions with earthquake effect was achieved on slope design 1V:2H. The SRF value at the portal outlet location is greater than the SRF value at the portal inlet location for the same slope design conditions indicating that the rock mass quality at the portal outlet location is better than the rock mass quality at the portal inlet location.